Soft Tissue Perineurioma in a Child With Neurofibromatosis Type 1: A Case Report and Review of the Literature. (September 2017) - Al-Adnani, Mudher
Soft tissue perineurioma is a rare benign peripheral nerve sheath tumor, especially in children. This manuscript presents an unusual case of soft tissue perineurioma in a 10-year-old boy with neurofibromatosis type 1. The patient presented with a lump in the region of the right breast. A subcutaneous, well circumscribed mass was removed. The cut surface was cream with a vaguely nodular appearance. Histology showed a spindle cell lesion with variable architecture and biphasic morphology. There was no nuclear atypia or pleomorphism. The differential diagnosis and other soft tissue lesions that can be seen in neurofibromatosis type 1 are discussed.